2009
DOI: 10.1038/jes.2009.13
|View full text |Cite|
|
Sign up to set email alerts
|

Risk assessment of pesticide exposure on health of Pakistani tobacco farmers

Abstract: Tobacco is an important cash crop of Pakistan. Pesticides are commonly used to increase the crop yield, but their health impact has not been studied yet. The objectives of the study were to determine the frequency of pesticide poisoning and to explore the knowledge, attitudes and practices (KAP) towards safety measures among the tobacco farmers in Swabi, Pakistan. One hundred and five tobacco farmers involved in pesticide application were randomly selected from two villages of district Swabi. A structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 26 publications
10
37
0
Order By: Relevance
“…45 Several other studies have also suggested a decrease in BChE level in response to exposure to organophosphates. 46,47 Similarly, in other parts of the developing world, including Mexico, Kenya, and Bangladesh, similar findings have been reported. 45,48,49 Varying responses of the populations exposed to insecticides by varying degree indicate that the impact rendered on part of these insecticides depends on a number of factors, such as the duration of exposure, the use of protective measures, etc.…”
Section: Discussionsupporting
confidence: 72%
“…45 Several other studies have also suggested a decrease in BChE level in response to exposure to organophosphates. 46,47 Similarly, in other parts of the developing world, including Mexico, Kenya, and Bangladesh, similar findings have been reported. 45,48,49 Varying responses of the populations exposed to insecticides by varying degree indicate that the impact rendered on part of these insecticides depends on a number of factors, such as the duration of exposure, the use of protective measures, etc.…”
Section: Discussionsupporting
confidence: 72%
“…19,28 In another study of tobacco growers involved in the application of pesticides during the tobacco harvest in two districts of Swabi, Pakistan, blood collection data for analysis of levels of plasma cholinesterase (PChE) found that 58 (55%) of PChE levels were normal, 35 (33%) presented mild intoxication and 12 (11%) presented moderate intoxication. 29 It was observed symptoms like headache, dizziness, vomiting, shortness of breath, muscle weakness and skin rashes during and after spraying pesticide in tobacco cultivation. 29 The most reported symptoms of poisoning among tobacco growers in this study are similar to those reported by other growers, such as headaches (60%), nausea and stomach ache (30%) and poisoning requiring hospitalization resulting from the use of pesticides (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are confirmed by those by Magauzi et al (2011) who finds that not being provided with personal protection equipment was associated with an abnormal cholinesterase activity, with the risk increasing from 1.07 to 3.68. Similarly, Khan et al (2010) reports that the absence of personal protection equipment influenced a decrease in cholinesterase activity even though the authors worked on seric acetylcholinesterase.…”
Section: Acetylcholinesterase Levelsmentioning
confidence: 99%